Terrorizing Images. Trauma and Ekphrasis in Contemporary Literature - Langas, Unni (Culture & Conflict, 2020)
This book combines two focal points: trauma and ekphrasis. It responds to the recognition of how terrorizing images permeate the public sphere in connection with traumatic experiences and conflicts and emphasizes the ways in which such images are described and interpreted by words. Contributors analyze the use of verbally represented images in a variety of literary texts, written in several different languages.